Primary sclerosing cholangitis – a comprehensive review - Karlsen, Tom H.; Folseraas, Trine; Thorburn, Douglas; Vesterhus, Mette (Journal of hepatology, 2017)
Primary sclerosing cholangitis (PSC) is a rare disorder characterised by multi-focal bile duct strictures and progressive liver disease. Inflammatory bowel disease is usually present and there is a high risk of cholangiocarcinoma and colorectal cancer. Most patients ultimately require liver transplantation, after which disease recurrence may occur. With limited therapeutic options and a lack of proven surveillance strategies, patients currently have significant unmet needs. In the present seminar, we provide a comprehensive review of the status of the field. We emphasise developments related to patient stratification and disease behaviour, and provide an overview of management options from a practical, patient-centered perspective. We survey advances made in the understanding of PSC pathogenesis and summarise the ongoing efforts to develop an effective therapy based on these insights.